Photoresponsive Polymeric Reversible Nanoparticles via Self-Assembly of Reactive ABA Triblock Copolymers and Their Transformation to Permanent Nanostructures - Ding, Liang (Materials (Basel), 2016)
Azobenzene-functionalized ABA triblock copolymers with controlled molecular weights are prepared first via a sequential ring-opening metathesis polymerization and acyclic diene metathesis polymerization in one-pot, which are readily converted, by a facile esterification, to the modified ABA triblock copolymers. Then, these reactive triblock copolymers can spontaneously self-assemble in a selective solvent to form reproducible and reversible polymeric core-shell nanoparticles. Finally, the stable and permanent shell-crosslinked nanoparticles are obtained by an intramolecular crosslinking reaction in dilute solution under UV light irradiation. These as-prepared polymeric nanoparticles and their precursor incorporating azobenzene chromophores exhibit distinct photoresponsive performance and morphological variation.